Bench behaviour of ice hockey coaches: Psychophysiological and verbal responses to critical game incidents - Kennedy, M. D.; Knight, C. J. (International Journal of Sports Science & Coaching, 2017)
The purpose of this study was to examine coaches' psychophysiological and verbal responses to different game situations. The in-game heart rate and verbal responses of three elite ice hockey coaches to four critical game incidents (Goals For/Against; Penalties Taken/Drawn) over four university women's games were assessed. Verbal comments were categorised using the Coach Behaviour Assessment System, and then comments and heart rate were sequenced to critical incidents recorded on video review. Overall, in-game heart rate was greater than rest and coaches were rarely silent. General encouragement and general commentary were the most common verbal comments. Two hundred and eight critical incident comments were recorded (Goals For/Against 34.6%; Penalties Taken/Drawn 65.4%) associated with a 10 bpm greater heart rate. Most common verbal responses to critical incidents were general commentary, silence and organisation. The type of comment was affected by the type of critical incident. In 78% of critical incidents, the type of comment made before incidents differed to type of comment after the incident, coaches rarely talked at the same time and silence was common. These novel findings are limited to ice hockey coaches given the small sample size. However, these results should encourage more research into the psychophysiological and verbal responses of coaches in other team sports real game situations to better understand in game coaching behaviour. ABSTRACT FROM AUTHOR